"I Know It's Not Saving a Life, but I Know I'm Doing Good…": The Peer Offender Prevention Service (POPS) at Stony Mountain Institution, Canada. Issue 5 (20th October 2021) - Walby, Kevin; Cole, Dwayne
ABSTRACT: There is a growing literature on prisoner peer support and mentoring to which this work contributes. This paper examines a form of prisoner peer mentoring at Stony Mountain Institution in the province of Manitoba, Canada. The Peer Offender Prevention Service (POPS) employs prisoners to provide support and mentorship for other prisoners throughout the prison. Based on interviews with POPS members and the POPS coordinator, this paper examines how the POPS initiative works and how POPS members feel about their experiences. We show that the work of POPS members is based on relationships, emotions, listening, compassion, and mutual aid among prisoners, all of which tends to be inhibited by the prison. This paper also analyzes the barriers that POPS members encounter and the challenges that the POPS initiative faces in the prison. In our discussion, we invoke the idea of fast policy to caution against the implementation of such programs in situations where sufficient resources, continuity, mentorship, and commitment are not established.